Determination of the Cut-off Value for Imatinib Plasma Levels Linked to Occurrence of Bone Pain in CML Patients - Hamza MS; Shouman SA; Abdelfattah R; Moussa HS; Omran MM (Dove Medical Press, 2022)
Marwa S Hamza,1 Samia A Shouman,2 Raafat Abdelfattah,3 Heba S Moussa,4 Mervat M Omran2 1Clinical Pharmacy Practice Department, Faculty of Pharmacy, The British University in Egypt, El-Sherouk City, Cairo, Egypt; 2Pharmacology Unit, Cancer Biology Department, National Cancer Institute, Cairo University, Cairo, Egypt; 3Medical Oncology Department, National Cancer Institute, Cairo University, Cairo, Egypt; 4Clinical Pathology Department, National Cancer Institute, Cairo University, Cairo, EgyptCorrespondence: Marwa S Hamza, Clinical Pharmacy Practice Department, Faculty of Pharmacy, The British University in Egypt, El-Sherouk City, Cairo, Egypt, Email marwa.hamza@bue.edu.egBackground: Imatinib is used to treat chronic myelogenous leukemia (CML). Variations in imatinib pharmacokinetics have been linked to genetic variations. That has an impact on imatinib response and adverse effects. Therefore, the aim of the study was to study bone pain as an adverse effect that occurs with imatinib and to investigate the risk factors for bone pain.Methods: The relationship between the peak and trough plasma concentrations of imatinib with bone pain as one of the most frequently occurring adverse effects was examined. Multiple linear regression analysis and binary logistic regression analysis were used to measure the impact of various patients' characteristics on both peak and trough imatinib concentrations and the risk of the occurrence of imatinib-induced bone pain.Results: As a side effect of imatinib, approximately 15% of patients with CML who were taking it experienced bone pain. This side effect was linked to the imatinib peak and trough plasma levels. Imatinib trough concentration was also linked to gender and the gene SLCO1B3-334T > G (TT). There were significant associations between peak concentrations and gender as well as patient weight.Conclusion: Higher peak and trough plasma concentrations of imatinib are linked with the risk of the occurrence of bone pain as a side effect of imatinib. Monitoring plasma concentrations of imatinib is useful to predict the bone pain of imatinib and to support quality of life in patients with CML.Keywords: imatinib, tyrosine kinase inhibitor, chronic myelogenous leukemia, trough plasma concentration, bone pain